Cingulate gyrus volumetry in drug free bipolar patients and patients treated with valproate or valproate and quetiapine - Atmaca, Murad; Ozdemir, Huseyin; Cetinkaya, Sebnem; Parmaksiz, Serap; Belli, Hasan; Poyraz, A. Kursad; Ogur, Erkin (Pergamon-Elsevier Science Ltd, 2007)
In patients with bipolar disorder, recent brain imaging studies have reported cingulate cortex volume change. We performed a volumetric magnetic resonance imaging (MRI) study to assess the subregions of the cingulate gyrus; left anterior cingulate (LAC), left posterior cingulate (LPC), right anterior cingulate (RAC), and right posterior cingulate (RPC). Our sample consisted of bipolar patients that are either unmedicated (n = 10), on valproate monotherapy (n = 10) or on valproate plus quetiapine (n = 10) versus healthy comparisons (n = 10). Thirty right-handed bipolar disordered patients were recruited. Of them, 10 were first-applying patients who never had taken any drug for this,condition (medication-naive group), 10 were on valproate treatment (valproate group) and 10 were on valproate plus quetiapine treatment (valproate plus quetiapine group). Cingulate gyrus volumes included both cortex and white matter. Drug-free patients had significantly smaller LAC and LPC volumes compared with valproate and valproate plus quetiapine groups and healthy controls. In addition, in post hoc comparisons, a trend toward significant difference was found between valproate plus quetiapine group and valproate group in regard to only LAC. Our findings suggest that valproate and quetiapine may have neuroprotective effects. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: MRI; cingulate cortex; volumetric; valproate; bipolar disorder; quetiapine